2019
DOI: 10.1016/j.seizure.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge, attitudes, and sociocultural factors on school enrollment of children with epilepsy in Gabon

Abstract: Purpose: Perceptions, beliefs and culture influence attitude towards epilepsy in sub-Saharan Africa. Misconceptions on epilepsy contribute to the persistence of negative attitudes in children with epilepsy particularly on their school enrollment. The aim of the study was to assess knowledge, attitudes, and sociocultural factors affecting schooling of children with epilepsy in Gabon. Meth ods: Teachers and health workers from two urban and four rural localities of Gabon were assessed using a self-administered q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…In this survey, most of the staff members' attitudes towards children with epilepsy were positive: 63.7% of the staff members allowed their children to survey and play with children with epilepsy, 70.1% of the staff members believed that seizures are not dangerous for other children, and 81.7% of the staff members agreed that most children with epilepsy can attend public school. These ndings are similar to another survey that found that the attitudes of teachers towards the enrollment of children with epilepsy in regular schools were positive [15]. However, some staff members' attitudes towards children with epilepsy were negative: 55.4% of teachers were afraid to have children with epilepsy in the classroom, and they wanted other students to come into the classroom only after the children with epilepsy were controlled or cured.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In this survey, most of the staff members' attitudes towards children with epilepsy were positive: 63.7% of the staff members allowed their children to survey and play with children with epilepsy, 70.1% of the staff members believed that seizures are not dangerous for other children, and 81.7% of the staff members agreed that most children with epilepsy can attend public school. These ndings are similar to another survey that found that the attitudes of teachers towards the enrollment of children with epilepsy in regular schools were positive [15]. However, some staff members' attitudes towards children with epilepsy were negative: 55.4% of teachers were afraid to have children with epilepsy in the classroom, and they wanted other students to come into the classroom only after the children with epilepsy were controlled or cured.…”
Section: Discussionsupporting
confidence: 84%
“…This rate was similar to the one found in survey in Togo [18], where only 30% of caregivers recognized that epilepsy could be cured by using medicines. However, Ibinga et al reported that 42.8% of the staff in their survey thought that epilepsy could be treated by modern or traditional medicine [15]. Seventeen percent of the staff in this survey thought that epilepsy is an infectious disease, which is higher than the same gure in a survey (10%) from Ethiopia [11].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Section A focused on the demographic information of the participants. Section B comprised 16 simple-choice questions on knowledge about the treatment of epilepsy that came from previously published papers [12][13][14][15][16]. Section B included the following aspects: (1) knowledge about the cognitive and behavioral characteristics of people with epilepsy (e.g., "Most children with epilepsy can go to public schools"); (2) knowledge about the causes and symptoms of and treatments for epilepsy (e.g., "For most patients with epilepsy, seizures can be controlled with drugs"); and (3) knowledge about seizure manifestations and the management of a seizure (e.g., "When you see a person having a seizure, can you stop the seizure") [16].…”
Section: Methodsmentioning
confidence: 99%